How to make the best use of immunotherapy as first-line treatment of advanced/metastatic non-small-cell lung cancer. (26th March 2019) - Peters, S; Reck, M; Smit, E F; Mok, T; Hellmann, M D
Abstract: Antibodies that target programmed death 1 (PD-1) or its ligand [programmed death ligand 1 (PD-L1)] have become a mainstay of first-line treatment of advanced/metastatic non-small-cell lung cancer (NSCLC) without targetable genetic alterations. In this review, we summarize results from recent clinical trials that have evaluated the anti-PD-1 antibodies pembrolizumab and nivolumab and the anti-PD-L1 antibodies atezolizumab and durvalumab as first-line treatment as monotherapy and in combination with chemotherapy, other immunotherapies, and antiangiogenesis agents. We discuss factors that may influence treatment selection, including patient baseline clinical and demographic characteristics, tumor histology, and biomarkers such as PD-L1 expression and tumor mutation burden. While immunotherapy has become a central component of first-line treatment of most patients with advanced NSCLC, important questions remain about how treatment should be managed for individual patients.